Analysis planning for life education model program private Islamic University in Indonesia - Hasrita Lubis (Proceedings of AICS - Social Sciences, 2013)
Long Life Learning (LLL) is growing rapidly as a focal point to the science and technology development. Therefore, universities as platform due to transforming the sciences in order to expand the knowledge and the latest technology to their customers are very integral. At the same time, college or other organizations are expected to be driven by the community that will be able to show the acceleration performance of science and technology. Thus, the existence ofthe community and the world are taken based on the ability to access knowledge and technology developments in the application of learning and readiness. In Indonesia, Islamic educations institutions such as private universities strive to be able to offer the appropriate programs with community and customers. In order to build the equivalence between the rapid development of science and technology, all the faculty members through various programs are continued to increase their knowledge. Academic staffs will be able to enhance their knowledge as on an ongoing basis when the universities perform an alysis of the need for academic skills, high working. Follow upon the results of the analysis skills needs to be realized throughout the academic programs of formal education or informal. Activity provides a hosted program the university will provide an opportunity for all faculty members to study upon the peak sustained optimal career. Instead the teacher will obtain a positive impact to be a quality college.Keywords: Long Life Education Program and University Islam Swasta.